The Influence of IT Governance Implementation on Firm Performance in Manufacturing Companies - Permatasari, Yani (Pusat P2M Politeknik Negeri Batam, 2025)
Abstract. This study aims to examine the effect of IT Governance implementation on firm performance in manufacturing companies listed on the Indonesia Stock Exchange for the years 2019-2020. The method used is quantitative descriptive method. This research will use multiple linear regression analysis. The research sample consists of manufacturing companies listed on the Indonesia Stock Exchange during the years 2019-2020. The independent variable studied is IT Governance with control variables being sales growth, advertising expense, research and development expense, and capital expenditure. The dependent variable is firm performance. The results obtained indicate that IT Governance does not influence firm performance. Sales growth has a negative but not significant effect on firm performance, while advertising expense has an influence on firm performance. However, research and development expense and capital expenditure do not have an influence on firm performance.